Research of the specificity of the development of international sea container transportation - Viktoriia Nykonchuk; Iuliia Samoilyk; Svitlana Pashkevych (Transport Technologies, 2022)
The rapid development of container transportation in the world requires acceptance of strategic decisions in the logistical and technical support of cargo delivery by sea transport with the aim of achieving effective development of the maritime logistics system and identifying the leaders of maritime logistics. The article considers the process of containerization in sea transport in the international context. This type of transportation has a lot of advantages over other types of cargo transportation, including low cost, large volumes of transportation, clear and unambiguous rules, legal norms of sea transportation, defined sea routes. In the course of the study, countries with access to the sea or the ocean were studied. Such countries include Germany, Sweden, Belgium, Austria, Japan, the Netherlands and Singapore - countries with a developed logistics system.